Actividad física y sus beneficios en la salud integral en los estudiantes de primero bachillerato de la Unidad Educativa Carlos Alberto Aguirre Avilés de la Parroquia La Unión cantón Babahoyo Provincia de Los Ríos - Avilés Baños, Pablo Marcelo (2019)
The research that supported the content of this article, presented as a central objective the determination of the benefits it brings to the integral health of the students of the First High School of the Carlos Alberto Aguirre Avilés Educational Unit, to achieve the stated purpose, methods were chosen from the theoretical and empirical level of scientific research. The research work that preceded the writing of this thesis summary presented an exploratory and descriptive design. For its development, 5 teachers and 45 students were selected, who provided the necessary information to comply with the planned objectives, the study was carried out between January 2019 and September of the year itself, the main processes were physical activity and comprehensive education. Chi-square was used to process the results derived from empirical techniques and methods. Among the main findings derived from the application of the technique already outlined, is a diagnosis of the existing situation, in relation to the subject under study, as well as the considerations of teachers and students in this regard, reaching the conclusion that effectively of physical activities improves the development of the levels of integral health.